Impact of Educational Videos on Dental Anxiety and Fear in Patients Undergoing Root Canal Treatment in Shiraz, Iran - mina shafa khah; Sareh Behzadi (Golestan University Of Medical Sciences, 2021)
Background and objectives: Dental anxiety refers to the fear associated with the idea of seeking dental care. It is the fifth most common cause of anxiety. The purpose of this study was to investigate efficiency of educational videos for reducing anxiety and fear in adult patients undergoing root canal treatment in private dental clinics. Methods: This was a quasi-experimental study with a pretest-posttest design. The statistical population consisted of all patients referred to private dental clinics in Shiraz (Iran) during the summer of 2016. Overall, 50 subjects were selected via the convenience sampling method. The subjects were randomly divided into an intervention group (n=25) and a control group (n=25). Both groups responded to two anxiety and fear questionnaires. Then, the intervention group participated in a video training session, while the control group did not receive any training. Subjects in both study groups once again completed the questionnaires. Data were analyzed in the SPSS (version 22) using one-way analysis of covariance and at statistical significance of 0.05. Results: After the intervention, the mean scores of fear and its components (avoiding dental treatment, physical symptoms caused by anxiety, and anxiety caused by dental stimuli) were significantly lower in the intervention group than in the control group (P<0.05). Conclusion: Based on the findings, it can be concluded that the educational video on root canal treatment could help reduce anxiety and fear in adult patients.